PENGEMBANGAN MODEL PROBLEM BASED LEARNING SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MENULIS TEKS EKSPOSISI DAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Nurhayatin, Titin; Regina, Frilia Shantika; Puspita, Yeni Cania (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2018)
This research is for study aims to test the problem-based learning model to improve the ability to write exposition and critical thinking skills. This research was conducted to find out the right model of learning to improve the ability to write expository text and critical thinking ability. The research method used in this research is quasi-experiment research method. The design of this research is quasi-experimental design. Based on the research findings it can be concluded that learning to write exposition text is considered difficult learning. In addition, students' interest in this text is low because writing expository texts is considered unpleasant. The structure and rules of exposition texts in this study include six aspects, namely (1) the title produced reflects the exposition text; (2) completeness of the text structure (thesis, argumentation, and reaffirmation); (3) the development of ideas is inductive and/or deductive; (4) the accuracy of the use of linguistic principles; (5) the presentation of arguments coherently in accordance with the theme; (6) conclusions in accordance with the arguments presented. After being treated in the form of application of problem-based learning model in the experimental class, learners have improved the ability to write expository texts and critical thinking skills when compared with control classes that are given learning in advance.